2x(4x-7)+3=(2x-7)(3x+4)+2x^2

Simple and best practice solution for 2x(4x-7)+3=(2x-7)(3x+4)+2x^2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(4x-7)+3=(2x-7)(3x+4)+2x^2 equation:


Simplifying
2x(4x + -7) + 3 = (2x + -7)(3x + 4) + 2x2

Reorder the terms:
2x(-7 + 4x) + 3 = (2x + -7)(3x + 4) + 2x2
(-7 * 2x + 4x * 2x) + 3 = (2x + -7)(3x + 4) + 2x2
(-14x + 8x2) + 3 = (2x + -7)(3x + 4) + 2x2

Reorder the terms:
3 + -14x + 8x2 = (2x + -7)(3x + 4) + 2x2

Reorder the terms:
3 + -14x + 8x2 = (-7 + 2x)(3x + 4) + 2x2

Reorder the terms:
3 + -14x + 8x2 = (-7 + 2x)(4 + 3x) + 2x2

Multiply (-7 + 2x) * (4 + 3x)
3 + -14x + 8x2 = (-7(4 + 3x) + 2x * (4 + 3x)) + 2x2
3 + -14x + 8x2 = ((4 * -7 + 3x * -7) + 2x * (4 + 3x)) + 2x2
3 + -14x + 8x2 = ((-28 + -21x) + 2x * (4 + 3x)) + 2x2
3 + -14x + 8x2 = (-28 + -21x + (4 * 2x + 3x * 2x)) + 2x2
3 + -14x + 8x2 = (-28 + -21x + (8x + 6x2)) + 2x2

Combine like terms: -21x + 8x = -13x
3 + -14x + 8x2 = (-28 + -13x + 6x2) + 2x2

Combine like terms: 6x2 + 2x2 = 8x2
3 + -14x + 8x2 = -28 + -13x + 8x2

Add '-8x2' to each side of the equation.
3 + -14x + 8x2 + -8x2 = -28 + -13x + 8x2 + -8x2

Combine like terms: 8x2 + -8x2 = 0
3 + -14x + 0 = -28 + -13x + 8x2 + -8x2
3 + -14x = -28 + -13x + 8x2 + -8x2

Combine like terms: 8x2 + -8x2 = 0
3 + -14x = -28 + -13x + 0
3 + -14x = -28 + -13x

Solving
3 + -14x = -28 + -13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13x' to each side of the equation.
3 + -14x + 13x = -28 + -13x + 13x

Combine like terms: -14x + 13x = -1x
3 + -1x = -28 + -13x + 13x

Combine like terms: -13x + 13x = 0
3 + -1x = -28 + 0
3 + -1x = -28

Add '-3' to each side of the equation.
3 + -3 + -1x = -28 + -3

Combine like terms: 3 + -3 = 0
0 + -1x = -28 + -3
-1x = -28 + -3

Combine like terms: -28 + -3 = -31
-1x = -31

Divide each side by '-1'.
x = 31

Simplifying
x = 31

You can always share this solution

See similar equations:

| 8x^3+10xy+6x^2y^5=0 | | 2X(X^2-4X+7)= | | 2x^2-5x-5=0 | | 2x^2-38x=7x^2-3x-24 | | 9p^2+18p=10 | | x^2-5x=6 | | 2x^2-4=-204 | | 2x^2-8=-170 | | x(5x+10)=2x^2-3x+30 | | 8x^2-8x-1=0 | | 2x^2-9x-2=0 | | 2x^2=10x+3 | | y^2-4y+8=0 | | 42t^2-13tv-42v^2= | | 6s^2-13s+6= | | 2w^2+9w+9= | | 4x^7-20x^5+16x^8= | | x^2-16=0 | | x^2=81 | | 3x^2+6x=0 | | x^2-7x=0 | | y^2+6y+8=0 | | 5x^4+31x^2+6=0 | | x^2-10-4x-11=0 | | 5x^3+(2x-12)=1 | | m^2-6m+8=0 | | m^2+10m+9=0 | | m^2+5m+6=0 | | 5x^2+10x+5=180 | | 6(1+8x^3)=9 | | x^3+6x^2=4x+24 | | 5x^2-7x+2=0 |

Equations solver categories